Assessment of Epstein-Barr Virus in Patients with Squamous Cell Carcinoma of the Larynx by Real-Time Polymerase Chain Reaction - Nouri, Masoumeh; Larizadeh, Mohammad Hasan; Mollaei, Hamid Reza; Mianroodi, Aliasghar Arabi; Bahador, Maryam; Shamsi, Sara (Journal of Contemporary Medical Sciences, 2021)
Objectives: This study was conducted to investigate the presence of Epstein- Barr virus (EBV) as a risk factor in laryngeal squamous cell carcinoma (SCC) and its effects on the pathological and clinical features of this disease. Methods: This cross-sectional study was conducted on 55 patients with histologically confirmed laryngeal SCC in the pathology department of Shafa and Afzalipour hospital, Kerman, Iran, referred to the radiation oncology department between January 2018 and May 2019 (study group). Thirty-five patients who underwent surgery for benign laryngeal lesions such as polyps, nodules, cysts, or granulomas were considered as the control group. Biopsy specimens of all subjects were examined for the presence of EBV DNA by Real-Time Polymerase Chain Reaction (RT-PCR). Demographic and clinicopathological characteristics of all patients were recorded and patients with laryngeal SCC were followed up regarding relapse. The data were analyzed using SPSS-17 software and descriptive and analytical statistics were done. Results: The incidence of EBV infection in patients with laryngeal SCC was 32.7 % (95% CI: 5 / 45- 21/8) and this amount was 2.9 % (95% CI: 0-8.6) in the control group. Based on multivariate logistic regression model, age (OR:1.05, 95% Cl: 1.00 - 1.10, P-value: 0.04), EBV (OR :9.76, 95% Cl: 1.07 - 88.59, P-value:0.04), smoking (OR: 6.82, 95% CI: 1.69 – 27.53, P-value: 0.007) and opium consumption (OR: 6.46, 95% CI: 1.36 - 30.66, P-value: 0.01) were determined as predictors of laryngeal SCC. In the patients’ group, the presence of EBV was associated with a higher lymph node stage, which was statistically significant but there was no significant relationship in terms of age, sex, tumor location and T stage and, relapse. Conclusion: This study showed an association between EBV as a risk factor and laryngeal SCC.